2022
DOI: 10.1177/15500594221093607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Temporal Window of Integration of Speech Sound on Mismatch Negativity

Abstract: Speech-sound stimuli have a complex structure, and it is unclear how the brain processes them. An event-related potential (ERP), known as mismatch negativity (MMN), is elicited when an individual's brain detects a rare sound. In this study, MMNs were measured in response to an omitted segment of a complex sound consisting of a Japanese vowel. The results indicated that the latency from onset in the right hemisphere was significantly shorter than that in the frontal midline and left hemispheres during left ear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…By analyzing the normalized power variance of electroencephalography (EEG), Aoki et al 7 demonstrated that EEG has another dimension, which contains much clinically useful information about cortical electrical activity. Hoshino et al 8 measured the mismatch negativity to an omitted segment of a complex sound consisting of a Japanese vowel in male healthy subjects. Their results suggest that the detection time for deviance may not be related to the stimulus ear.…”
mentioning
confidence: 99%
“…By analyzing the normalized power variance of electroencephalography (EEG), Aoki et al 7 demonstrated that EEG has another dimension, which contains much clinically useful information about cortical electrical activity. Hoshino et al 8 measured the mismatch negativity to an omitted segment of a complex sound consisting of a Japanese vowel in male healthy subjects. Their results suggest that the detection time for deviance may not be related to the stimulus ear.…”
mentioning
confidence: 99%